Lower and middle atmosphere and ozone layer responses to solar variation - Elias, Ana Georgina (2010)
Global warming in the troposphere and the decrease of stratospheric ozone concentration has become a major concern to the scientific community. The increase in greenhouse gases and aerosols concentration is believed to be the main cause of this global change in the lower atmosphere and in stratospheric ozone, which is corresponded by a cooling in the middle and upper atmosphere. However, there are natural sources, such as the sun and volcanic eruptions, with the same ability to produce global changes in the atmosphere. The present work will focus on solar variation and its signature in lower and middle atmosphere parameters. The Sun can influence the Earth and its climate through electromagnetic radiation variations and also through changes in the solar wind which causes geomagnetic storms. The effects of both mechanisms over the lower and middle atmosphere and ozone layer will be discussed through an overview of selected papers, which by no means cover this subject that is extremely wide and complex. A fundamental understanding of the atmosphere response to solar variations is required for understanding and interpreting the causes of atmospheric variability. This is an essential focus of climate science, which is seeking to determine the extent to which human activities are altering the planetary energy balance through the emission of greenhouse gases and pollutants.